BOOK REVIEW. KATRANDJIEV, V. (2011) THE FOREIGN POLICY OF THE EUROPEAN UNION. - BULGARIA. SOFIA: MILITARY PUBLISHING HOUSE - Stefanov, Румен (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
отсутствует